2013
DOI: 10.1016/j.rehab.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacities and exercise tolerance in neuromuscular diseases: A descriptive study

Abstract: The main limitation factor in exercise tests is peripheral. Ventilatory and cardiovascular limitations can nonetheless be added on; while they are absent when the patient is at rest, they are unmasked in effort situations. Exercise tests could be of great interest in screening and managing the relevant pathologies. Multicenter studies on homogeneous populations could facilitate definition of the procedures specific to exercise tests for patients suffuring from neuromuscular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Patient #5 improved in all the parameters and was the only one to improve in both 6MWD and peakVO 2 . Similar inconsistency in respiratory limitation parameters were reported post 36 month of ERT treatment and may indicate decreased sensitivity of these respiratory limitation parameters in advanced disease …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Patient #5 improved in all the parameters and was the only one to improve in both 6MWD and peakVO 2 . Similar inconsistency in respiratory limitation parameters were reported post 36 month of ERT treatment and may indicate decreased sensitivity of these respiratory limitation parameters in advanced disease …”
Section: Discussionsupporting
confidence: 69%
“…To the best of our knowledge, no studies have been published evaluating pediatric Pompe patients using CPET as a tool for exercise capacity evaluation. Rapin et al reported CPET results in metabolic myopathies in adult patients; 5/9 did not meet the criteria for a maximal test . Bartels et al evaluated nine children with muscular dystrophy and concluded that criteria for maximal effort were primarily developed to detect exercise limitations in patients with cardiac and pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients an insufficient effort, as shown by a low RER, could at least partly warrant the low peak VE and HRR values; however, that was not the case for other subjects. Accordingly, a recent paper on neuromuscular patients, including four subjects affected by glycogenosis, reported that limited exercise tolerance was multifactorial due to both an insufficient Vt recruitment and a low cardiac output [23]. The insufficient Vt recruitment may be related to respiratory muscles' weakness, while cardiac abnormalities could depend on central deconditioning due to sedentary lifestyle or to autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] The compliance of the patient group and healthy subjects was high. Moreover, sugar-free chewing gum contains polyols which are alcohol derivates of sugar.…”
Section: Discussionmentioning
confidence: 97%